2011
DOI: 10.1021/ie200296e
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Prediction of Water Content in Alkanes Using a Molecular Theory

Abstract: We present a predictive model for the saturated water concentration in n-alkanes based on a theoretical equation of state for the hydrocarbon rich phase and a water equation of state for the aqueous phase. By considering a polar or associating component at low concentration in a nonpolar solvent, we can neglect polar or hydrogen bonding interactions in the hydrocarbon rich phase, thus reducing the number of fitted parameters. The approach allows us to determine the intrinsic pure component equation of state pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 51 publications
3
24
0
Order By: Relevance
“…Though the LB rule may not be very accurate, the water-alkane interaction energy here is too high (ξ = 1.67) to be attributed to the inadequacy of the LB rule. Values of LJ parameters close to the ones we find here were obtained in the theoretical work of Emborsky et al 29 when they calculated the solubility of water in alkanes using the PC-SAFT model for alkanes. They found that a value of ε W /k = 207 K was required to match the solubility of water in the different alkanes.…”
Section: Resultssupporting
confidence: 88%
“…Though the LB rule may not be very accurate, the water-alkane interaction energy here is too high (ξ = 1.67) to be attributed to the inadequacy of the LB rule. Values of LJ parameters close to the ones we find here were obtained in the theoretical work of Emborsky et al 29 when they calculated the solubility of water in alkanes using the PC-SAFT model for alkanes. They found that a value of ε W /k = 207 K was required to match the solubility of water in the different alkanes.…”
Section: Resultssupporting
confidence: 88%
“…To minimize the number of variables, we first treat water as a single sphere with a chain length m = 1. Second, we employ the results of Emborsky and Chapman(EC) 23 who obtained the reference system energy εww for water in PC-SAFT by regressing to water solubility in alkane data. As water is dilute in the hydrocarbon phase, their value of reference energy (εww = 209.84 kB) will correspond to   As can be seen, both cases give similar errors in the description vapor pressure; however, case II gives a substantial improvement in the overall description of the liquid densities (see Fig.…”
Section: Iii: Resultsmentioning
confidence: 99%
“… was fit to solubility water solubility in HC data. 23 The test is then, how well does the theory take this information and predict the solubility of HC in the water phase? As can be seen, the new approach (case II) is much more successful.…”
mentioning
confidence: 99%
“…These authors have demonstrated that accurate modeling of two and three‐phase equilibria in aqueous systems of various hydrocarbons can be achieved by implementing the APACT EoS with zero and close to zero values of binary parameter k 12 . Later on, further progress in improving the predictive character of estimating phase equilibria in alkane‐water mixtures has been achieved by Emborsky et al who have fitted the nonpolar and non‐associating PC‐SAFT EOS 7 parameters for pure water to its solubility data in liquid alkanes at ambient conditions without additional determination of the binary adjustable parameters. This approach has been successfully extrapolated to predict water solubility in n ‐alkanes at the higher temperatures and pressures.…”
Section: Introductionmentioning
confidence: 99%